2014
DOI: 10.5039/agraria.v9i2a3237
|View full text |Cite
|
Sign up to set email alerts
|

Manutenção e reprodução de Anomalocardia brasiliana em condições laboratoriais

Abstract: RESUMOO presente estudo analisou as taxas de filtração e a ingestão do bivalve Anomalocardia brasiliana (Gmelin, 1791) (Veneridae) e avaliou sua reprodução em laboratório. Os exemplares foram coletados na praia do Mangue Seco, 7°49'39.80"S e 34°50'13.55"O Pernambuco, Brasil. Para avaliar a taxa de filtração e ingestão, foram realizados três experimentos independentes: Experimento 1 -com presença de luz (2 mil Lux) e ausência de luz; Experimento 2 -com três temperaturas distintas 23,5, 27 e 30 ºC; Experimento 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Lavander et al (2014) apontam que o melhor desenvolvimento da filtração nesses animais é quando eles são submetidos a uma temperatura de 27ºC, com uma concentração de salinidade de 30 g.L -1 . Na APA Barra do Rio Mamanguape, as medidas morfométricas foram similares entre as duas unidades (Mamanguape e Controle), mostrando que não existe relação entre a atividade de catação do marisco com o tamanho médio das conchas das populações.…”
Section: Discussionunclassified
“…Lavander et al (2014) apontam que o melhor desenvolvimento da filtração nesses animais é quando eles são submetidos a uma temperatura de 27ºC, com uma concentração de salinidade de 30 g.L -1 . Na APA Barra do Rio Mamanguape, as medidas morfométricas foram similares entre as duas unidades (Mamanguape e Controle), mostrando que não existe relação entre a atividade de catação do marisco com o tamanho médio das conchas das populações.…”
Section: Discussionunclassified
“…The condition factor provides an index of the optimal period for investment in reproduction (sexual maturation and the production of gametes), as well as the nutritional condition and stress of the organisms (Absher & Christo 1993, Aswani et al 2004). The higher values recorded in the dry season were due to the larger mass of soft parts in the cockles harvested, which indicates a greater investment in reproductive structures (gonads and gametes) or optimal conditions for feeding and growth, possibly related to the higher salinity of the estuary (Lavander 2013, Lima et al 2010. Silva (2014b) recorded continuous reproduction in L. pectorina on Algodoal-Maiandeua Island, although mature individuals were more common at the end of the dry season, and spawned individuals in the rainy season.…”
Section: An Acad Brasmentioning
confidence: 97%
“…While no data are available on the tolerance of L. pectorina to salinity, A. brasiliana is known to survive in a salinity range of 17-42, although values below 24 may provoke osmotic stress, and an increase in mortality (Leonel et al 1983, Monti et al 1991. Laboratory studies have shown that, while A. brasiliana tolerates an ample variation in salinity, phytoplankton filtration is optimal at a salinity of between 30 and 35, while the animals stop feeding at salinities below 20 (Lavander 2013, Lima et al 2010. Salinity may vary from 7 to 24 during the rainy season in the Marapanim estuary, where Algodoal-Maiandeua Island is located (at its outer limit), and from 27 to 35 during the dry season (Aviz et al 2016).…”
Section: An Acad Brasmentioning
confidence: 99%
“…One promising species for tropical aquaculture ( Lagreze-Squella et al, 2018 ) is the clam Anomalocardia flexuosa , which is distributed from the Caribbean to Brazil ( Abbott, 2011 ), and plays an important role in feeding and in the income of traditional communities ( Rios, 2009 ). Hatchery production methodologies based on feeding, maturation, reproduction, larviculture and settlement events under controlled laboratory conditions have been developed for this species ( Lavander et al, 2014 ; Lagreze-Squella et al, 2018 ; Lima et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%